As contribuições do PIBID/UNIOESTE na formação de professores: subprojetos de matemática de Cascavel e Foz do Iguaçu - Andretti, Evandro Carlos (2017)
This research aims to understand how the ex - pibidiano - teacher applies in the day to day school the theoretical and practical knowledge learned during his participation in the Institutional Program of Initiation to Teaching - PIBID - of the State University of the West of Paraná - UNIOESTE - of the Mathematics courses of the Campi de Cascavel and Foz do Iguaçu. In order to identify the contributions and limitations of this training process, in the eyes of the graduates of the program, we seek to answer the following guiding questions: How does the teacher who lived PIBID / UNIOESTE in his undergraduate course evaluate PIBID's contributions to teaching Mathematics in the future as a teacher? What is the contribution of PIBID in initiating teaching of ex-pibidians? The documents, projects and publications were used for the recognition of the scenario, identification of the dynamics and particularities of the program in the national, institutional and in each of the subprojects. Firstly, we sought the students who graduated from the Mathematics courses of Campi Cascavel and Foz do Iguaçu that met the following criteria: to have participated in the program for a time equal to or greater than twelve months and to be effectively in the classroom. Two teachers from Foz do Iguaçu and three teachers from Cascavel participated in the study. Data were collected through a semi-structured interview. After collecting the data the work was concentrated on observing if the national, institutional and of each subproject objectives were contemplated in the speech of the graduates. The characteristics and feelings of beginning teachers indicated by the literature are revealed throughout the initiation process of the subjects, beginning in the experiences in the program what follows in the first years of teaching, however with some indications that some difficulties are overcome by the learning generated in that Training, which contributed to the professional integration. The program also seeks to provide the articulation between theory and practice to the licenciandos, seeks to overcome the dichotomies between school mathematics and the academic mathematics of initial formation that reflects directly in professional practice. The teachers participating in the research highlight continuing education, as they reflect on their practice, perceive their trajectories, their gaps in initial and continuing training, and difficulties stemming from inexperience. However, they are reflective and interested in becoming better teachers and developing professionally in their careers.